The Effect of Bortezomib on Expression of Inflammatory Cytokines and Survival in a Murine Sepsis Model Induced by Cecal Ligation and Puncture - Han, Sang Hoon; Kim, Jin Seok; Woo, Jun Hee; Jeong, Su Jin; Shin, Jeon-Soo; Ahn, Young Soo; Kim, June Myung (Yonsei medical journal, 2015)
Although the proteasome inhibitor known as bortezomib can modulate the inflammatory process through the nuclear factor-kappa B signaling pathway, the immunomodulatory effect of pre-incubated bortezomib has not been fully evaluated for inflammation by infectious agents. Therefore, we evaluated the effect of bortezomib on the expression of inflammatory cytokines and mediators in macrophage cell lines and on survival in a murine peritonitis sepsis model. Bortezomib was applied 1 hr before lipopolysaccharide (LPS) stimulation in RAW 264.7 cells. The cecal ligation and puncture (CLP) experiments were performed in C57BL/6J mice. Pre-incubation with bortezomib (25 nM or 50 nM) prior to LPS (50 ng/mL or 100 ng/mL) stimulation significantly recovered the number of viable RAW 264.7 cells compared to those samples without pre-incubation. Bortezomib decreased various inflammatory cytokines as well as nitric oxide production in LPS-stimulated cells. The 7-day survival rate in mice that had received bortezomib at 0.01 mg/kg concentration 1 hr prior to CLP was significantly higher than in the mice that had only received a normal saline solution of 1 mL 1 hr prior to CLP. In addition, the administration of bortezomib at 0.01 mg/kg concentration 1 hr before CLP resulted in a significant decrease in inflammation of the lung parenchyma. Collectively, pretreatment with bortezomib showed an increase in the survival rate and changes in the levels of inflammatory mediators. These results support the possibility of pretreatment with bortezomib as a new therapeutic target for the treatment of overwhelming inflammation, which is a characteristic of severe sepsis.